LoRaWAN Monitoring System for Emergency Vital Signs in Pusu River - Mohamed Hadi Habaebi; Nur Sakinah Kosnin; Shihabeldin Fadli Yousif Hasan; Md. Rafiqul Islam (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Sungai Pusu is the river that passes through the IIUM Gombak campus. The river has been having a cloudy appearance for years hence it is needed to quantify the vital signs such as pH, temperature, and turbidity because these are the vital signs indicating the health of a river. Currently, there a lot of monitoring systems however the available monitoring systems do not support long-range communication and consume a lot of power. The data need to be transmitted at a long-range as it is being monitored remotely at a long distance. Therefore, a river pollution monitoring system must be developed to track the emergency vital signs (EVSs) of the river water The EVs include pH, temperature as well as turbidity. This project capitalizes on the long-range communication and low power consumption LoRaWAN system. The prototype monitoring station design can read the important EVSs of the river such as temperature, pH level, and turbidity. The sensors are connected to a microcontroller board. The readings of the EVSs are transmitted by the LoRa gateway which is forwarding the data to The Things Network Server. A graphical representation of the data is displayed on Ubidots. The results attained quantify the contribution of the IIUM populace to Sungai Pusu Pollution and raise awareness. It is also important to discuss the possibilities to the pollution of the river to see how one’s action could contribute to it. A statistical data of the results is as important so that an overall result can be deduced. Based on the results, the pH is decreased 1.32 pH, the temperature is increased by 2.29°C, and turbidity is decreased by 0.44 NTU throughout the monitoring period. In the future, six more monitoring stations will be added to accommodate KL River of Life (RoL) EVSs too.